Pembangunan e-tutoran pemodelan 3 dimensi : satu pendekatan kreatif - Syadiah Nor Wan Shamsuddin
This research is: purposely to develop an e-tutor for learning and teaching of 3Dmodeling using theories and approaches that are relevance and the usage ofmultimedia elements in software can give dissimilarity and increase students'interests. Therefore the rationale of developing this E-tutor because most of elearningnowadays are not systematic and well structured and did not emphasize ontheories and strategies of teaching and learning. The result of this research is aconceptual model from well research of literature review and a prototype of 3dmodeling E-SITES courseware. The development of this E-SITES coursewareconsists of theories such as cognitive, constructivism, elaboration and andragogy.Creativity approach is also implemented to this software based on recent creativitymodels so that objects can be drawn creatively. Dick & Carey(1996) and IDI(1991)development model methodology are used in developing this courseware as aguideline. However, researcher had combine and made changes purposely for thisdevelopment.Target users are students from higher learning institutions. E-SITESconsists of several modules such as Tutorial Module, Task Module, Utility Moduleand Forum Module. It is emphasis on Tutorial Module that is consists of three levels:Basic, Medium and Complex that focus on 3d modeling from basic to complex basedon Malay heritage such as keris, wau;. congkak, gong and rebana to nourish thevaluable heritage so it will not be neglected by the time period. The learning andteaching of this software hopefully can help the learning of 3d modeling to be morecreative and also the experiences will be more enjoy and effective.